The protective effect and crucial biological pathways analysis of Trametes lactinea mycelium polysaccharides on acute alcoholic liver injury in mice based on transcriptomics and metabonomics - Jinbin Hao; Liyun Ye; Guoliang Meng; Yanjiao Song; Junsheng Fu; Xiaoping Wu (Food Science and Human Wellness)
Trametes lactinea mycelia polysaccharides (TLMPS) have a wide range of bioactivities. The potential mechanisms of action of TLMPS against acute alcohol-induced liver injury in vivo were investigated by analyzing the physical and chemical properties of TLMPS and its protective effects on a mouse model of alcoholic liver injury. TLMPS protected the liver against alcohol-induced injury, as evidenced by the reduced alcohol-induced elevation of the liver index, serum biochemical indices, and maintenance of hepatic morphology. Potential mechanisms were analyzed using transcriptome and metabolome analyses. The transcriptome data revealed the involvement of many differentially expressed genes in chemical carcinogenesis, drug metabolism, and metabolism of xenobiotics by cytochrome P450. The metabolome analysis revealed that TLMPS significantly regulated specific metabolites in the liver, including organic acids, lipids, nucleosides, and organic oxygen compounds. KEGG enrichment analysis revealed the significant involvement of different metabolites in choline metabolism, ATP-binding cassette transporters, and glycerophospholipid metabolism. Assessment of the changes in gene expression and metabolites revealed the significantly different expression of several genes encoding key enzymes and metabolites in choline metabolism pathway. The collective findings confirmed that choline metabolism plays an important role in the protective effects of TLMPS against acute alcoholic liver injury.